2013
DOI: 10.1159/000350461
|View full text |Cite
|
Sign up to set email alerts
|

Brain Diffusion Changes in Obstructive Sleep Apnoea Syndrome

Abstract: Background: Obstructive sleep apnoea syndrome (OSAS) is a disorder characterized by repeated apnoeic episodes during sleep. Neurocognitive changes secondary to OSAS are likely to occur due to hypoxia in certain brain locations. Advances in magnetic resonance imaging technology, such as diffusion-weighted imaging (DWI), enable non-invasive and accurate identification of OSAS-induced changes. Objective: We aimed to use DWI to investigate changes in the brain secondary to hypoxia in OSAS. Methods: Eighty-eight pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Consistent with previous findings in patients with COPD, widespread increases in ADC values have also been observed in patients with stroke (Schlaug et al., 1997; Yang & Rosenberg, 2011) and in patients with obstructive sleep apnea syndrome (Emin Akkoyunlu et al., 2013). In a previous study, a decrease in FA values in patients with COPD was observed (Zhang et al., 2012b).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous findings in patients with COPD, widespread increases in ADC values have also been observed in patients with stroke (Schlaug et al., 1997; Yang & Rosenberg, 2011) and in patients with obstructive sleep apnea syndrome (Emin Akkoyunlu et al., 2013). In a previous study, a decrease in FA values in patients with COPD was observed (Zhang et al., 2012b).…”
Section: Discussionmentioning
confidence: 99%
“…A number of processes, possibly including intermittent cerebral ischemia, marked blood pressure swings, and CO 2 changes accompanying repeated apnea episodes during sleep in OSAS patients cause structural injury and dysfunction367. Although atrophy and neuronal loss in the thalamus and putamen of OSAS patients have been reported earlier15161718, the underlying pathophysiology underlying the injury is complex, with the putamen also showing regions of volume increase suggestive of inflammation or glial activation, as opposed to cell death or reduced myelin integrity. We found significantly lower tCho/Cr ratios in the bilateral thalamus and right putamen, tNAA/Cr and NAA/Cr in left thalamus, GABA/Cr in bilateral putamen, PE/Cr in left putamen and GPC/Cr in the right thalamus in the OSAS patients, as compared to healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Both structural and functional neuroimaging studies show brain injury in the putamen91516, and thalamus in OSAS patients1718, but information on metabolite levels in damaged areas is sparse1920. Magnetic resonance spectroscopy (MRS) is a noninvasive neuroimaging tool that allows assessment of cerebral metabolite changes, providing information on neuronal cellular viability, cellular energetics, and cellular membrane status20, and may assist understanding of the nature of the altered thalamic and putamen structures in OSAS.…”
mentioning
confidence: 99%
“…Routine magnetic resonance imaging (MRI) examinations may not show cerebral damage in OSAS patients, but advanced MRI techniques can reveal neurochemical and structural changes in various regions of the brain (4,5). In the literature, many studies using non-invasive and quantitative methods such as diffusion-weighted imaging (DWI), MR spectroscopy (MRS) and T2 relaxometry have been used to identify alterations in the brains of OSAS patients (3)(4)(5)(6)(7)(8). DWI is a non-invasive technique, which can demonstrate cerebral damage resulting from some disease processes (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…The diffusion of water molecules is affected by microenvironmental architecture, and the rate of diffusion, referred to as the apparent diffusion coefficient (ADC), can be measured quantitatively (12). Although DWI and ADC measurement are commonly used for differentiating a variety of brain lesions, to our knowledge, there are only two studies evaluating the efficacy of these methods in defining the structural changes in OSAS (6,8).…”
Section: Introductionmentioning
confidence: 99%